Optimal port allocation scheme for deflection-routed networks-on-chip - Stojanovic, Igor; Jovanovic, Milica; Djosic, Sandra; Djordjevic, Goran Lj (The Journal of supercomputing, 2021)
Deflection routing is considered a promising approach for improving the energy efficiency of networks-on-chip (NoCs) because of its hardware simplicity and minimal buffer requirements. The major weakness of the deflection routing is poor performance under high network load because of excessive flit deflections that occur in routers as a result of resolving frequent port conflicts. In this paper, we propose a design solution for optimal port allocation in permutation-network-based deflection NoC routers. The proposed solution requires 3.3× fewer hardware resources compared to a naïve implementation of the optimal port allocation scheme while providing 38.6% higher network throughput than a commonly used suboptimal port allocation scheme. We also present a novel low-cost suboptimal port allocator, which improves the network throughput by 17.4% over the conventional port allocator with comparable hardware complexity.